TUGAS DAN TANTANGAN GURU: MEMBANGUN KUALITAS GURU MENUJU PENGEMBANGAN PENDIDIKAN BERMUTU - Masayu Gay (EDUKASI, 2015)
The teacher responsible for realizing quality of education. Quality of education can be realized, when the teacher is always in synergy with the tasks development of quality of education in the form of design elements in developing education programs in the form of (1) the content of teacher education; (2) the learning process; (3) the context of learning, which is based on the essentials of teacher education programs. In addition, teachers are required to optimize its main task as a teacher of teachers and build capabilities, which include: content knowledge that is taught; conceptualization level; the ability of teachers in implementing the learning process; last interpersonal communication capability. Capabilities associated with the business knowing yourself and attempt to build responsibility to the environment, and realized the teacher as researcher on classroom action research. This research aims give way to the teachers to develop quality in order to develop quality of education.Key words: Quality of teachers, development, quality of education